Implementasi Jalur Komunikasi Global System Mobile (GSM) Untuk Kontrol Robot Jarak Jauh Berbasis Mikrikontroller Atmel89S52 - Wire Bagye (Jurnal Informatika dan Rekayasa Elektronik, 2018)
Some of the previous research builds controlled robots using devices with limited distance. The remote controlled robot controls the control distance along the rays of the sender's Infrared (IR) ray is not blocked by a 20 meters long Infrared (IR) receiver. The blue tooth controlled robot has a control distance of 40 meters. The controlled Robot Wireless Fidelity controls the maximum range of range specifications of the Access point range used. Maximum coverage ranges for outdoor access points as far as 15 Kilometers. The next research have to do with a longer distance control than previous research. In this research is Built a robot controlled by utilizes of the Global System Mobile (GSM) communication line. This project uses two Hand phones as a sender and the other one to become receiver. Hand phone sender function is sends control signal to receiver phone. Signals sent are DTMF signals (Dual Tone Multiple Frequency). There are 9 signals control with difference function. Those functions are (1) Turn left (2) Right turn (3) Left rewind (4) Right rewind (5) Rear left (6) Rear Right (7) Stop (8) Move forward (9) Move backward. On the mobile phone receiver signal DTMF in the form of analog signal is converted by Integrated Circuit (IC) MT8870p become Signal Digital. Digital signal from IC MT 8870p is used to be input of Atmel89s52 microcontroller. Atmel89s52 output has not been able to be used for DC motor drive signal so that used transistors amplifier to control the relays. Relay as an electronic switch to connect and disconnect the DC voltage to the motor so that the DC motor can be two-way. DC motors rotating clockwise and counterclockwise. This rotation is used as a robot movement. The research results shown that 9 DTMF key tones can be used to control the robot through the GSM line. Long of distance control as far as location that is accessible GSM signal from BTS (Base Transceiver Station). Further research needs to be done to transmit video signals so that it can be done long distance visual monitor on the movement of the robot.